A step towards cinacalcet testing for the diagnosis of primary hyperparathyroidism: comparison with the standardized intravenous calcium loading. A pilot study. (5th March 2015) - Cailleux, A.; Vuillermet, P.; Basuyau, J.P.; Ménard, J.F.; Lefebvre, H.; Kuhn, J.M.; Prévost, G.
Summary Objective A calcium load to suppress parathyroid hormone (PTH) secretion can help to perform the diagnosis in some case of primary hyperparathyroidism (PHPT) with atypical presentation. A similar test with calcimimetic, which avoids hypercalcaemia, would be of interest. Our proof of concept study was conducted to compare firstly the results of a single‐dose cinacalcet testing with those of the standardized short‐time calcium load in healthy control (HC) and secondly the results of the single‐dose cinacalcet testing in HC and in PHPT. Methods Twelve HCs received in a random order, at a 2‐week interval, either 0·33 mmol/kg calcium gluconate intravenously for 3 h, or a single oral dose of 30 mg or 60 mg cinacalcet. Twelve PHPTs received 30 mg cinacalcet and twelve other PHPTs 60 mg cinacalcet orally. Calcaemia and serum PTH levels were measured basally and then hourly for 6 h. Results In HC, plasma calcium did not significantly change after cinacalcet intake, whereas calcaemia rose up to 3·47 ± 0·05 mmol/l (mean ± SEM) at the end of the calcium load. PTH dropped from basal level to a similar extend (≥80%) with 60 mg cinacalcet and calcium load, whereas the decrease was significantly lesser (P < 0·01) with 30 mg cinacalcet. In PHPT, serum PTH levels dropped by 44·8 ± 6·9% and 58·2 ± 5·3% 1 h after the respective intake of 30 and 60 mg cinacalcet. One hour after the oral intake of 60 mg cinacalcet, serum PTH levels were <8 ng/l in HC and ≥8 ng/l in PHPT. Conclusion Sixty milligrams of cinacalcet provides similar results as the standardized calcium load test; PHPT patients have a lower response to 60 mg cinacalcet than HC.